The impact of COVID‐19 upon the delivery of exercise services within cystic fibrosis clinics in the United Kingdom. (1st March 2022) - Tomlinson, Owen W.; Saynor, Zoe L.; Stevens, Daniel; Urquhart, Don S.; Williams, Craig A.
Abstract: Objectives: The COVID‐19 pandemic has resulted in unprecedent changes to clinical practice, and as the impact upon delivery of exercise services for people with cystic fibrosis (CF) in the United Kingdom was unknown, this was characterised via a national survey. Methods: An electronic survey was distributed to healthcare professionals involved in the exercise management of CF via established professional networks. Results: In total, 31 CF centres participated. Findings included significant reductions in exercise testing and widespread adaptation to deliver exercise training using telehealth methods. Promisingly, 71% stated that they would continue using virtual methods of engaging patients in future practice. Conclusion: These findings highlight adaptation to the COVID‐19 pandemic and the need to develop sustainable and standardised telehealth services to manage patients moving forwards.